Scope 3: what question are we trying to answer? - Ballentine, Roger (Frontiers in Sustainable Energy Policy, 2024)
Once a little-scrutinized and largely optional aspect of corporate greenhouse gas emissions disclosure, Scope 3 emissions accounting and reporting is now a common element of voluntary climate best practice and is increasingly being adopted as part of new mandatory corporate climate disclosure policies. As Scope 3 disclosure becomes more central to what companies are asked (or required) to do, we perhaps should ask anew what exactly it is we are trying to accomplish. While those NGOs and other stakeholders that designed the Scope 3 framework and who have included it in highly influential corporate leadership programs were well-intentioned, it is becoming clear that the system as designed is ill-suited to serve its fundamental purpose: driving corporate actions to reduce, avoid, and remove greenhouse gas emissions. Scope 3 inventories are often seen as an end in and of themselves, yet from a climate perspective, they are only tools -and only useful if they help lead to positive emissions impact. What companies are asked to do regarding value chain emissions is not adequately aligned with what climate science demands. Therefore, greenhouse gas accounting, disclosure, and leadership programs and rules must modernize their approaches to Scope 3. Options include: limiting data collection requirements to seeking actionable, primary data; using proxy data only as a baseline from which the demonstrated impact of emissions-reducing interventions can be credited by target setting and leadership programs; and by fully embracing the use of verified market mechanisms to enable investments in positive emissions impact.